Frontal and temporal sources of mismatch negativity in healthy controls, patients at onset of schizophrenia in adolescence and others at 15 years after onset - Oknina, Ljubov B.; Wild-Wall, N.; Oades, R. D.; Juran, S. A.; Röpcke, B.; Pfüller, Ute; Weisbrod, Matthias; Chan, E.; Chen, E. Y. H. (Schizophrenia research, 2005)
Mismatch negativity (MMN) is an event-related potential measure of auditory change detection. It is widely reported to be smaller in patients with schizophrenia and may not improve along with otherwise successful clinical treatment. The main aim of this report is to explore ways of measuring and presenting four features of frequency-deviant MMN dipole sources (dipole moment, peak latency, brain location and orientation) and to relate these to the processes of psychopathology and illness progression. Data from early onset patients (EOS) at the start of the illness in adolescence, and others who had their first break in adolescence 15 years ago (S-15Y) were compared with two groups of age-matched healthy controls (C-EOS, C-15Y). A four-source model fitted the MMN waveform recorded from all four groups, whether MMN amplitude was more (EOS) or less (S-15Y) reduced. The locations were in the left superior temporal and anterior cingulate gyri, right superior temporal and inferior/mid frontal cortices. Dipole latencies confirmed a bottom-up sequence of processing and dipole moments were larger in the temporal lobes and on the left. Patients showed small dipole location changes that were more marked in the S-15Y than the EOS group (more rostral for the left anterior cingulate, more caudal for the right mid-frontal dipole) consistent with illness progression. The modelling of MMN dipole sources on brain atlas and anatomical images suggests that there is a degree of dissociation during illness between small progressive anatomical changes and some functional recovery indexed by scalp recordings from patients with an onset in adolescence 15 years before compared to adolescents in their first episode.
Available online 11 November 2004
Gesehen am 22.12.2021